Mineralogical determination of Bemololo, Miandrivazo and Analavory clays by X-ray diffraction for applications - Elidon, Ramahandry Jean; Baholy, Robijaona Rahelivololoniaina; Andrianirina, Randriantsimbazafy; Wega, Razafindramanga Athou; Rokiman, Letsara; Rija, Rabearisoa Solotiana; Ngbolua, Koto-te-Nyiwa; Aurélien, Mandimbiiharison (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
After characterizing the clay minerals from the Bemololo (BMLL), Miandrivazo (MNDV), and Analavory (ANLV) deposits using X-ray diffraction (XRD), dye absorption experiments and photochemical screening analyses were conducted to determine the potential applications for each clay. XRD analysis revealed that the Bemololo deposit comprises the following mineral compositions: BMLL 001 is rich in muscovite; BMLL 002 contains a mixture of vermiculite, sepiolite, and amphibole; BMLL 003 is composed of kaolinite and chlorite; and BMLL 004 is predominantly kaolinite. For the Miandrivazo deposit, MNDV 001 is a mixture of kaolinite, muscovite, and chlorite; MNDV 002 contains chlorite and muscovite; and MNDV 003 comprises kaolinite and muscovite. The Analavory deposit features ANLV 001, which contains aragonite and calcite, and ANLV 002, identified as vermiculite clay. Dye absorption experiments indicated that BMLL 001, BMLL 002, and BMLL 003 have potential applications in water treatment, particularly in the removal of unwanted dyes or ions. Additionally, photochemical screening revealed the presence of deoxyose in BMLL 004, while BMLL 002, ANLV 002, and ANLV 001 were found to contain tannins.